Mensuração da qualidade no atendimento: - Araújo, Taynara da Silva Araújo (Universidade Federal do Tocantins, 2023)
This study aimed to describe the importance of measuring the quality of customer service, from then onwards, the verification of the quality of the service level was carried out in a stationery located in Araguaína-TO. The research carried out aimed to assess the quality of some important aspects for a good service and analyze the requirements of stationery customers. It was proposed to carry out a bibliographical research in books, articles, websites used to guide this work and the application of a questionnaire containing five important dimensions of the SERVQUAL scale to obtain the quantitative data needed in this work. With this, it was possible to understand that identifying the expectations and perceptions of customers is extremely important to help in taking corrective measures where the company is not exceeding expectations and to improve aspects with a low level of service.